Timeless: A Large Sample Study on the Temporal Robustness of Affective Responses - Postzich, Christopher; Blask, Katarina; Frings, Christian; Walther, Eva (Frontiers in Psychology, 2016)
Emotion and its effects on other psychological phenomena are frequently studied by presenting emotional pictures for a short amount of time. However, the duration of exposure strongly differs across paradigms. In order to ensure the comparability of affective response elicitation across those paradigms, it is crucial to empirically validate emotional material not only with regard to the affective dimensions valence and arousal, but also with regard to varying presentation times. Despite this operational necessity for the temporal robustness of emotional material, there is only tentative empirical evidence on this issue. To close this gap, we conducted a large sample study testing for the influence of presentation time on affective response elicitation. 240 emotional pictures were presented for either 200 ms or 1000 ms and were rated by 302 participants on the core affect dimensions valence and arousal. The most important finding was that affective response elicitation was comparable for 200 ms and 1000 ms presentation times, indicating reliable temporal robustness of affective response elicitation within the supra-liminal spectrum. Yet, a more detailed look on the data showed that presentation time impacted particularly on high arousing negative stimuli. However, because these interaction effects were exceedingly small, they must be interpreted with caution and do not endanger the main finding, namely the quite reliable temporal robustness of affective response elicitation. Results are discussed with regard to the comparability of affective response elicitation across varying paradigms.